2021
DOI: 10.3390/ani11030820
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148a Regulates the Proliferation and Differentiation of Ovine Preadipocytes by Targeting PTEN

Abstract: MicroRNAs (miRNAs) have been found to be involved in lipid deposition and metabolism. However, there have been no reports on the roles of miR-148a in the proliferation and adipogenesis of preadipocytes in sheep. In this study, the expression of miR-148a was profiled in the eight tissues of Tibetan ewes and differentiated preadipocytes, and the role of miR-148a in differentiation and proliferation of ovine preadipocytes was investigated using Oil Red O staining, CCK-8, EdU staining, cell cycle detection, and RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…21 while miR-148a expression continues to rise in mid-lactation with the potential to target and regulate fatty acid metabolism for infant growth and development. 22 Moreover, the targets and expression levels of the milk-derived miRNAs may also vary when delivered to different tissues or cells. Therefore, improving the accuracy and sensitivity of target gene prediction is a significant challenge for achieving miRNA-targeted regulation in the future.…”
Section: Introductionmentioning
confidence: 99%
“…21 while miR-148a expression continues to rise in mid-lactation with the potential to target and regulate fatty acid metabolism for infant growth and development. 22 Moreover, the targets and expression levels of the milk-derived miRNAs may also vary when delivered to different tissues or cells. Therefore, improving the accuracy and sensitivity of target gene prediction is a significant challenge for achieving miRNA-targeted regulation in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of nutrigenomic regulation of the transcription confirmed that these genes play a critical role in the regulation of lipid metabolism processes in sheep and could be associated with fatty acid profiles in milk and meat. Ovine LPL gene should also be studied due to its expression to microRNA-148a [ 55 ]. SCD and BTN1A1 genes were not found to be differentially expressed when comparing two Spanish sheep breeds [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table S3. Sheep tails from a transcriptomic perspective: microRNA profiles [242][243][244][245][246][247][248][249][250][251][252][253][254]. Table S4.…”
Section: Supplementary Informationmentioning
confidence: 99%